RESEARCH OF DYNAMICS OF TEACHERS’ READINESS FOR ORGANIZATION OF DISTANCE AND BLENDED LEARNING - Natalia M. Averianova (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The effectiveness and efficiency of distance and blended learning depends on educators and their ability to use ICT in an online learning environment. This testifies to the need for qualitative research on the direction of progress and the breadth of changes in the personal and activity sphere of the participants in the educational process as a result of changes in the organization of learning using scientific methods. We conducted a study of the dynamics of teachers’ readiness to organize distance learning and blended learning after two years of quarantine restrictions. We used a questionnaire survey, testing, interviews, analytical observations, collection of independent characteristics of analyzes of the products of activity, which students give in the regard of the given research question. The most important indicators of readiness to realize ICT opportunities in the process of online learning were monitored. Research questions were studied among teachers, those questions related to the main goals of using blended and distance learning, online educational services, the degree of implementation and ICT tools in this process, the factors that interfere with successful online work. Students acted as independent experts on those issues. They had the opportunity to assess the level of complexity of electronic learning, the results of their own distance learning, and the idea of continuing distance learning. As a result of monitoring, we recorded an increase in the level of teachers’ readiness to use ICT in the context of blended and distance learning. It manifested itself in changing the understanding of goals, rethinking of perspectives, the expansion of the ICT tools used. We have noted the transition from static cases of academic disciplines to a dynamic combination of cases and Internet technologies. The results of the study have revealed a number of problems, including insufficient technological support of the educational process, a large percentage of teachers who have psychological difficulties in the constant learning process of using new ICT tools, the adaptation problems of teachers and students associated with the increase in the number of hours of distance work and the use of new forms of distance pedagogical communication.